Ghana 3D Telemedicine International MDT: A Proof-of-concept study - Fowers, Spencer; Britto Mattos Lima, Andrea; Spina, Thiago V.; Tittsworth, David; Hoak, Amber; Cutler, Ben; O'Dowd, Christopher; Johnson, Johnny (Journal of Plastic, Reconstructive, and Aesthetic Surgery, 2023)
A real-time 3D Telemedicine system - leveraging Microsoft’s HoloportationTM communication technology – enabled an international multidisciplinary team meeting (MDT) to consult with complex reconstructive patients prior, during, and after an overseas surgical collaboration. Methods A proof-of-concept international 3D MDT clinic took place in November 2022, between Canniesburn Plastic Surgery Unit, UK and the National Reconstructive Plastic Surgery and Burns Centre, Korle Bu Teaching Hospital, Ghana. The 3D system was utilised 1) pre-visit to assess patients and enable logistical planning, 2) on-site in Ghana to further allow patients to see themselves and proposed operations in 3D, and 3) post-visit to debrief team and patients. Results 4 Ghana patients were followed through their patient journey (mandibular ameloblastoma, sarcoma thigh, maxillary tumour, sarcoma back). 13 participants (4 patients, 4 Ghana clinicians, 5 UK clinicians) completed feedback on the 3D MDT. Outcome measures were rated highly with satisfaction 84.31/100, perceived benefit 4.54/5, overall quality 127.3/ 147 (Telehealth Usability Questionnaire), and usability 83.2/100 (System Usability Scale). These data show close alignment with that previously published on high income countries. Conclusions This novel technology has potential to enhance delivery of overseas surgical visits to low-to-middle income countries (LMIC), by improving planning, informed discussion with patients, expert consensus on complex cases, and fostering engagement with professionals who may be thousands of miles away. This is the first demonstration that real-time 3D Telemedicine can both work, and enhance care within an International MDT clinic, and may thus enable change in the approach to overseas surgical collaborations.